Pengaruh Kepemimpinan dan Penilaian Prestasi Kerja Terhadap Motivasi Kerja Karyawan pada Kantor PDAM Tirta Taman Sari Kota Madiun - Maya Hanjar Elifa Purnomo (Universitas PGRI Madiun, 2018)
The formulation of the problem in this research is whether there is an influencebetween leadership and performance appraisal of work motivation. The purpose of thisstudy was to determine the influence between the influence between leadership andperformance appraisal of work motivation where empirical study in this research is PDAMTirta Taman Sari Madiun Office. This research uses quantitative method. collectiontechniques in this study with questionnaires and observations. The method of analysis used isdescriptive method by using multiple linear regression for hypothesis testing. The result ofhypothesis testing shows that leadership and job performance appraisal have an effect onemployee work motivation at PDAM Tirta Taman Sari Office of Madiun City. The value ofFcount is 21,371, while Ftable is 3.06, Sighitung is 0,000 while Sigprob is 0.05. This meansthat the value of Fcount > Ftable (21,371 3.06) or Sighitung Sigtabel (0.000 0,05), or itcan be concluded reject HO, meaning there is total influence between leadership and jobperformance appraisal to work motivation at PDAM Tirta Office Taman Sari Madiun City.